The Influence of Work Loyalty on Employee Work Productivity at the Pln Up2d Makassar Office - Zulfiani Zulfiani; Samsul Rizal; Muh. Nur. R (Journal Social Society, 2026)
The urgency of this study is to identify how work loyalty contributes to improving employee productivity and organizational performance at PLN UP2D Makassar.. In the context of increasing organizational demands for efficiency and service reliability, particularly in public utility sectors, employee productivity has become a critical factor in ensuring sustainable performance. One of the key determinants influencing productivity is work loyalty, which reflects employees’ commitment, responsibility, and emotional attachment to the organization. However, empirical evidence on the role of work loyalty in enhancing employee productivity in state-owned enterprises remains limited. Therefore, this study aims to examine the effect of work loyalty on employee productivity at PLN UP2D Makassar. This study employs a quantitative approach with a cross-sectional design, involving 43 employees selected through purposive sampling. Data were collected using structured questionnaires based on a Likert scale and analyzed using descriptive statistics and simple linear regression. The findings reveal that work loyalty has a positive and statistically significant effect on employee productivity, as indicated by a t-value of 7.413 and a significance level below 0.05. The regression analysis shows that an increase in work loyalty leads to a proportional increase in productivity, with a regression coefficient of 0.757. Furthermore, the coefficient of determination (R² = 0.573) indicates that 57.3% of the variation in employee productivity can be explained by work loyalty, while the remaining 42.7% is influenced by other factors not examined in this study. These results highlight the importance of employee commitment, responsibility, and emotional attachment in enhancing work performance. The study contributes to human resource management literature by providing empirical evidence on the role of work loyalty as a key driver of productivity, particularly in public service organizations. In conclusion, strengthening work loyalty is essential for improving employee productivity and achieving sustainable organizational performance.